Collapse of Self-Interacting Scalar Field in Anti-de Sitter Space - 蔡荣根 季力伟 杨润秋 (Communications in theoretical physics, 2016)
The gravitational collapse of a massless scalar field with a self-interaction term λφ~4 in anti-de Sitter space is investigated.We numerically investigate the effect of the self-interaction term on the critical amplitudes,forming time of apparent horizon,stable island,and energy transformation.The results show that a positive λ suppresses the formation of black hole,while a negative λ enhances the process.We define two susceptibilities to characterize the effect of the self-interaction on the black hole formation,and find that near the critical amplitude,there exists a universal scaling relation with the critical exponent α ≈ 0.74 for the time of black hole formation.